Mark L. Bristol papers - Bristol, Mark L. (Mark Lambert), 1868-1939.; Bristol, Helen Moore
Correspondence, diaries, speeches, reports, memoranda, official dispatches, appointment sheets, press releases, scrapbooks, and other papers pertaining primarily to Bristol's diplomatic and naval career. Documents his duties as commander of the U.S. Naval Detachment in Turkish Waters and as U.S. Office of the High Commissioner for Turkey, 1919-1927; his role in the Conference on Near Eastern Affairs held in Lausanne, Switzerland, in 1922-1923; and his command of the U.S. Navy Asiatic Fleet, 1927-1929. Includes Bristol's observations on foreign relations between the United States, Turkey, and the Middle East; conditions in the Middle East following World War I; aspects of the Russian revolution including the refugee situation in southern Russia; and political events in China, 1927-1929. Also reflects Bristol's interests following his retirement including the control of narcotics, his work with the American Peace Society and the Democratic League of the District of Columbia, and his efforts to establish a shipbuilding operation in Florida. Includes the papers of Bristol's wife, Helen Moore Bristol, and other family papers. Correspondents include Philip Andrews, Constantine Brown, Josephus Daniels, Ralph Earle, Albert Gleaves, Joseph C. Grew, Richmond Pearson Hobson, Charles B. McVay, Jr., Henry Croskey Mustin, Holden Chester Richardson, William Sowden Sims, and Lucien Irving Thomas.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Naval officer and diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Andrews, Philip, -- 1866-1945 -- Correspondence; Brown, Constantine, -- 1889-1966 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Earle, Ralph, -- 1874-1939 -- Correspondence; Gleaves, Albert, -- 1858-1937 -- Correspondence; Grew, Joseph C. -- 1880-1965 -- Correspondence; Hobson, Richmond Pearson, -- 1870-1937 -- Correspondence; McVay, Charles B. -- 1868-1949 -- Correspondence; Mustin, Henry Croskey, -- 1874-1923 -- Correspondence; Richardson, Holden Chester, -- 1878- -- Correspondence; Sims, William Sowden, -- 1858-1936 -- Correspondence; Thomas, Lucien Irving, -- 1876-1942 -- Correspondence; Bristol family; United States. -- Naval Detachment in Turkish Waters; United States. -- Navy; United States. -- Navy -- Foreign service -- Mediterranean Region; United States. -- Navy. -- Asiatic Fleet; United States. -- Office of the High Commissioner for Turkey; American Peace Society; Democratic League of the District of Columbia; Diplomatic and consular service, American -- Turkey; Drug control; Peace -- Societies, etc; Shipbuilding industry -- Florida; China -- Politics and government -- 1912-1949.; Middle East -- History -- 20th century; Middle East -- Foreign relations -- United States; Soviet Union -- History -- Revolution, 1917-1921.; Soviet Union -- History -- Revolution, 1917-1921 -- Refugees; Turkey -- Foreign relations -- United States; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Middle East; United States -- Foreign relations -- Turkey; Diplomats; Naval officers